Crypto anarchy, cyberstates, and pirate utopias - Ludlow, Peter (Digital communication., 2001)
In Crypto Anarchy, Cyberstates, and Pirate Utopias, Peter Ludlow extends the approach he used so successfully in High Noon on the Electronic Frontier, offering a collection of writings that reflects the eclectic nature of the online world, as well as its tremendous energy and creativity. This time the subject is the emergence of governance structures within online communities and the visions of political sovereignty shaping some of those communities. Ludlow views virtual communities as laboratories for conducting experiments in the construction of new societies and governance structures. While many online experiments will fail, Ludlow argues that given the synergy of the online world, new and superior governance structures may emerge. Indeed, utopian visions are not out of place, provided that we understand the new utopias to be fleeting localized "islands in the Net" and not permanent institutions. The book is organized in five sections. The first section considers the sovereignty of the Internet. The second section asks how widespread access to resources such as Pretty Good Privacy and anonymous remailers allows the possibility of "Crypto Anarchy"--Essentially carving out space for activities that lie outside the purview of nation states and other traditional powers. The third section shows how the growth of e-commerce is raising questions of legal jurisdiction and taxation for which the geographic boundaries of nation-states are obsolete. The fourth section looks at specific experimental governance structures evolved by online communities. The fifth section considers utopian and anti-utopian visions for cyberspace. Contributors Richard Barbrook, John Perry Barlow, William E. Baugh Jr., David S. Bennahum, Hakim Bey, David Brin, Andy Cameron, Dorothy E. Denning, Mark Dery, Kevin Doyle, Duncan Frissell, Eric Hughes, Karrie Jacobs, David Johnson, Peter Ludlow, Timothy C. May, Jennifer L. Mnookin, Nathan Newman, David G. Post, Jedediah S. Purdy, Charles J. Stivale